Representations of the Tree of Life in Ancestors’ Symbolics - Loredana Gașpar (Anastasis: Research in Medieval Culture and Art, 2022)
From time immemorial, our predecessors have projected an entire series of symbols on trees, so that through them, man can become part of what is sacred, thus being able to absorb a speck of the sacred. Therefore, elements of the sacred are identified in a series of established trees. The tree’s roots travel in the hypogeal world, the trunk takes part at the terrestrial life, while the branches raise towards the sky, thus forming a ladder which can be climbed by the man who escapes the mundane present and enters the other world. The three fundamental phases from human existence: birth, marriage and funeral are similar to the three component parts of the tree, but in the same time, they are also marked by the presence of the Tree during the three ceremonies: at birth, wedding and funeral. The cosmic tree is always situated in a sacred space, we may either refer to the sky tree or the life tree with its substitutes – the tree of birth, of wedding, fertility, of judgement, funeral, or we may have in view the place where the column of the sky is erected with its substitutes – the buttresses of life, the columns of judgement, preventive pales, but also the simulacra of the sky column – the countryside troițǎ1, road columns, grave columns. Even nowadays, there are various sacred connections established by human beings for different trees: the apple tree is of life and wisdom, dominating the landscape from Paradise, the sycamore maple is the one used for making the semantron and the maple is the tree with a divine valence, the fir is the double of human life, the grapevine is a symbol of immortality, the May Tree or the maypole watches over and protects the household from evil forces, the pine cone is an expression of the world renewal. Our ancestors connected their faith to trees that were their church and body and they also hoped that, when they would die, the tree would be the bridge that would make the transition towards the Other World. There are many and varied ways of expression of this symbol and there are numberless its codes. The artist from ancient times and even the nowadays peasant differently represent the Tree of Life, depending on the context, but there are also multiple ways of exhibiting; still, its essence has remained sacred and not altered.